Composition and reactivity of morphologically distinct charred materials left after slash-and- burn practices in agricultural tropical soils - Rumpel, C.; González Perez, J.A.; Bardoux, G.; Largeau, C.; González Vila, F.J.; Valentin, Christian (2007)
The composition of black carbon (BC) was studied up to now using laboratory experiments, which often fail to reproduce conditions occurring in natural fires. We sampled plant material and two BC fractions produced during slash and burn agriculture from two adjacent sites. A coarse fraction (CF), most probably derived from twigs and stems, was differentiated from lighter, fluffy fine material (FF). The samples were analysed for elemental and isotopic composition and their reactivity using acid hydrolysis and acid dichromate oxidation. The chemical composition of the samples was studied by 13C CPMAS NMR spectroscopy and analytical pyrolysis. The lignin content of the samples was determined after CuO oxidation. The two BC fractions were higher in carbon than the plant material. On an ash-free basis the CF and FF sampled from the two different sites had remarkably similar elemental contents. Stable isotope ratios of carbon showed enrichment or depletion depending on the morphological fraction under C3 vegetation. The ratios tended to be depleted in 13C with regards to the plant material in both fractions for samples taken under C4 vegetation. The reactivity of BC towards dichromate oxidation and acid hydrolysis was lower for CF compared to FF. 13C CPMAS NMR spectroscopy showed that BC fractions were aromatic but could also show substantial contribution from alkyl and O-alkyl C. Analytical pyrolysis and CuO oxidation indicated that part of the lignin backbone was remaining in all BC